Izmail Sreznevsky and Slovenian - Irina Makarova Tominec (Jezikoslovni zapiski)
The Slovenian language played an important role in the history of Russian- Slovenian scholarly contact. The unique linguistic material of Slovenian attracted the research of important nineteenth-century Russian linguists. This article discusses in greater detail how complex issues were resolved with regard to studying Slovenian dialects, their scholarly description and classification, and the borders between them. It is interesting that an important contribution to solving these issues was made by the Russian scholar Izmail Sreznevsky and somewhat later by his student Jan Baudouin de Courtenay.